Monkeys - Courtauld, Sarah; Illustrated by Howarth, Daniel (London Usborne Publishing, 2009)
A captivating look into the amazing world of monkeys, how they sleep, eat and play.
Include Illustrations
Keywords: Monkeys -- Primates